A life-threatening, massive subcutaneous hematoma caused by trauma in a patient with neurofibromatosis type 1: a case report and literature review - Zhang, Lu; Wang, Xingtong; Yin, Huinan; Chu, Wanli; Zhang, Ming; Zhu, Minhui; Shi, Zhiyuan; Chen, Zequn; Zhao, Fan (Frontiers in Oncology, 2024)
Background Neurofibromatosis type 1 (NF1) is an autosomal dominant disease that can give rise to the formation of vascular lesions in affected individuals. These lesions, whether occurring spontaneously or as a result of trauma, have the potential to cause severe and even fatal hemorrhage. Case description We presented a case demonstrating the most extensive hematoma ever documented in a patient with NF1, resulting from a minor trauma. He experienced hemodynamic instability due to severe anemia. Arteriography revealed a rupture in the intercostal artery, which was successfully treated through interventional embolization to stop the hemorrhage. Additionally, we implemented a refined surgical approach, beginning with suturing, followed by the meticulous resection of necrotic and aberrant tissues, thereby markedly diminishing bleeding. Conclusion Minor trauma may cause severe bleeding in patients with NF1, which can be life-threatening. Timely diagnosis of NF1 and effective hemostatic techniques are key to successful treatment.